Bridge on air ; Fort Santiago ; A woman's world [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Looks at the application for satellite facilities of ABS-CBN and its rejection by the Department of Transportation and Communication. Updates the Fort Santiago diggings for gold. A feature on women with universal job. Focuses on a postman, a mechanic and a pilot.
Bridge on air (16 min.) -- Fort Santiago (17 min. ) -- A woman's world (16 min.)
VHS.
Keywords: Marcos, Ferdinand E., 1917-1989.; ABS-CBN (Television station : Quezon City).; Telecommunication -- Philippines; Franchises (Retail trade) -- Philippines).; Treasure trove -- Philippines -- Manila; Women -- Social conditions. -- Philippines; Stereotype (Psychology).; Women -- Employment -- Philippines